Critical Success Factors for Six Sigma Implementation in Large-scale Turkish Construction Companies - Taner, Mehmet Tolga (International Review of Management and Marketing, 2013)
This paper aims to investigate the Critical Success Factors (CSFs) for the successful introduction of Six Sigma in large-scale Turkish construction companies. A survey-based approach is used in order to identify and understand the current quality practices. CSFs and impeding factors are identified and analysed. Involvement and commitment of top management, linking quality initiatives to customer and linking quality initiatives to supplier are found to be the most important CSFs to the construction companies. Leadership and commitment of top management, cross-functional teamwork and commitment of middle managers are found to be the most CSFs for successful introduction of Six Sigma, whereas lack of knowledge of the system to initiate and complacency are found to be hindering its implementation. High costs and high amount of waste are found to lower the performance of Turkish construction companies. Keywords: Six Sigma; construction industry; large-scale companies; Turkey JEL Classifications: L15; L74